Evidence for extensive hybridisation and past introgression events in feather grasses using genome-wide SNP genotyping - Evgenii Baiakhmetov (BMC, 2021)
Abstract Background The proper identification of feather grasses in nature is often limited due to phenotypic variability and high morphological similarity between many species. Among plausible factors influencing this issue are hybridisation and introgression recently detected in the genus. Nonetheless, to date, only a bounded set of taxa have been investigated using integrative taxonomy combining morphological and molecular data. Here, we report the first large-scale study on five feather grass species across several hybrid zones in Russia and Central Asia. In total, 302 specimens were sampled in the field and classified based on the current descriptions of these taxa. They were then genotyped with high density genome-wide markers and measured based on a set of morphological characters to delimitate species and assess levels of hybridisation and introgression. Moreover, we tested species for past introgression and estimated divergence times between them. Results Our findings demonstrated that 250 specimens represent five distinct species: S. baicalensis, S. capillata, S. glareosa, S. grandis and S. krylovii. The remaining 52 individuals provided evidence for extensive hybridisation between S. capillata and S. baicalensis, S. capillata and S. krylovii, S. baicalensis and S. krylovii, as well as to a lesser extent between S. grandis and S. krylovii, S. grandis and S. baicalensis. We detected past reticulation events between S. baicalensis, S. krylovii, S. grandis and inferred that diversification within species S. capillata, S. baicalensis, S. krylovii and S. grandis started ca. 130–96 kya. In addition, the assessment of genetic population structure revealed signs of contemporary gene flow between populations across species from the section Leiostipa, despite significant geographical distances between some of them. Lastly, we concluded that only 5 out of 52 hybrid taxa were properly identified solely based on morphology. Conclusions Our results support the hypothesis that hybridisation is an important mechanism driving evolution in Stipa. As an outcome, this phenomenon complicates identification of hybrid taxa in the field using morphological characters alone. Thus, integrative taxonomy seems to be the only reliable way to properly resolve the phylogenetic issue of Stipa. Moreover, we believe that feather grasses may be a suitable genus to study hybridisation and introgression events in nature.